The Role of General Attitudes and Perceptions Towards Vaccination on the Newly-Developed Vaccine: Results From a Survey on COVID-19 Vaccine Acceptance in China - Jing, Rize; Fang, Hai; Wang, Hufeng; Wang, Jiahao (Frontiers in Psychology, 2022)
Background: Vaccination has been considered one of the most effective public health interventions. In the context of the global epidemic of coronavirus disease 2019 (COVID-19), it remains unclear what role general vaccination attitudes and perceptions have on the acceptance of COVID-19 vaccine. Objective: This study aims to explore the impact of general attitudes and perceptions towards vaccination on the acceptance of newly-developed vaccine, taking the COVID-19 vaccines as an example. Method: A cross-sectional survey was conducted among 2013 Chinese adult participants. The generalized order logistic regression and path analysis models were performed to analyze the impacts of general attitudes and perceptions towards vaccination on the acceptance of the COVID-19 vaccine. Results: The prevalence of hesitancy to vaccination among the Chinese adult population is 49.9% in general. The general perceptions of vaccination were associated with the corresponding perceptions of the COVID-19 vaccine. A “no hesitancy” attitude towards vaccination is a significant determinant (aOR=1.77, 95% CI=1.36-2.31) of future COVID-19 vaccination compared to vaccine refusers, and perceptions of COVID-19 vaccine remains significant determinant for the acceptance of COVID-19 vaccine. Path analysis indicates that the perceptions of importance and safety of vaccination have a positive overall effect on the acceptance of the COVID-19 vaccine, and that the general perceptions of vaccination as a whole on each measure indirectly influence the acceptance of the COVID-19 vaccine. Conclusions: The general attitudes and perceptions towards vaccination were associated with the those of the COVID-19 vaccine and future vaccination intention. To prepare for possible emergence of diseases in the future, routine health campaigns should be launched by the relevant government departments and vaccination authorities to enhance the overall awareness and knowledge of vaccination among the public and to ensure their optimal vaccination experience. In addition, targeted knowledge dissemination and mass mobilizations should be urged for those newly-developed vaccines when some specific infectious diseases emerge, such as the COVID-19 at present.